Exploring Gender Construction in the Disney Movie Mulan (2020) by Niki Caro - Firdiansyah, Firdiansyah (English Literature Department, Adab and Humanities Faculty, 2024)
Gender inequality occurs through many things, including being formed, socialized, strengthened, even socially or culturally constructed, through the teachings of religion and the state. This study attempts to investigate the kinds of gender constructions pursued in the Mulan movie, to find out gender construction’s impacts on the character in the Mulan movie and to describe the Mulan efforts to fight for the inequalities in the Mulan movie by Niki Caro. This research uses Alice Eagly’s theory and this research uses descriptive qualitative research. The object of this research is in the Mulan movie by Niki Caro. The data are collected by documentation technique. Then, the data were analyzed by applying Gender construction theory and qualitative research. The research finding show; first, there are two kinds of gender constructions pursued in the Mulan movie; society and gender roles and gender at home. Second, there are two Gender construction’s impacts on the character in the Mulan movie by Niki Caro, they are dependency of decision making and psychological pressures. The last, there are two Mulan’s efforts to fight for the inequalities in the Mulan movie by Niki Caro, they are having bravery to take men’s duties and expressing rational opinions